2005
DOI: 10.1614/wt-04-214r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Glufosinate Antagonizes Clethodim Control of Goosegrass (Eleusine indica)

Abstract: Because of a previously reported antagonism of clethodim activity by other herbicides, greenhouse experiments were conducted to determine goosegrass control with clethodim and glufosinate postemergence alone, in tank mixtures, and as sequential treatments. Herbicide treatments consisted of glufosinate at 0, 290, or 410 g ai/ha and clethodim at 0, 105, or 140 g ai/ha, each applied alone, in all possible combinations of the above application rates, or sequentially. Glufosinate at either rate alone controlled goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
3
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 34 publications
(49 reference statements)
3
46
3
5
Order By: Relevance
“…These data indicate that to minimize yield loss, control of volunteer corn is needed before it is 46 cm tall, although the plant can be controlled by later-season applications. Unlike a study by Burke et al (2005) that reported antagonism when clethodim and glufosinate were applied together to goosegrass (Eleusine indica) vs. clethodim applied alone, we saw . 96% control with EPOST timings of either rate.…”
Section: Resultscontrasting
confidence: 98%
“…These data indicate that to minimize yield loss, control of volunteer corn is needed before it is 46 cm tall, although the plant can be controlled by later-season applications. Unlike a study by Burke et al (2005) that reported antagonism when clethodim and glufosinate were applied together to goosegrass (Eleusine indica) vs. clethodim applied alone, we saw . 96% control with EPOST timings of either rate.…”
Section: Resultscontrasting
confidence: 98%
“…This is consistent with previous studies that have reported antagonism of the ACCase-inhibiting herbicides when tank mixed with some broadleaf herbicides (Culpepper et al 1998(Culpepper et al , 1999Holshouser and Coble 1990;Vidrine et al 1995). For instance, Burke et al (2005) reported a 50% reduction in goosegrass . An early-POST followed by a late-POST application of glufosinate improved volunteer corn control !…”
Section: Resultssupporting
confidence: 92%
“…According to the label, a single glufosinate application up to 740 g ai ha À1 can be made in soybean, with a cumulative 1,340 per growing season (Anonymous 2014). Earnest et al (1998) (Burke et al 2005;Gardner at al. 2006).…”
mentioning
confidence: 99%
“…Goosegrass control efficacy is effected, among other variables by the maturity of the plant. Previous research noted a reduction in control at the one-to two-tiller and four-to six-tiller growth stage, compared with the two-to four-leaf growth stage (Burke et al, 2005). McCarty (1991) noted differences in goosegrass control with diclofop based on goosegrass mowing height.…”
mentioning
confidence: 94%